Molecular and quantitative genetic analysis of the neotropical tree Jacaranda micrantha Cham. - Sanson, Daniela; Homczinski, Isabel; Roque, Rafael Henrique; Bobrowski, Rogério; Peres, Fabiana Schmidt Bandeira; Tambarussi, Evandro Vagner [UNESP] (FapUNIFESP (SciELO), 2024)
Backgrounds: Urban and peri-urban fragments are vital for biodiversity conservation, requiring genetic assessment of tree species in fragmented forests. The aim of this study was to analyze the genetic variability and diversity for adult individuals of J. micrantha along an urban-rural gradient in the Araucaria Forest. Fifteen individuals were sampled, with five from each remaining forest type. Initially, 10 ISRR primers were tested. Five mother trees were chosen from each site (urban, peri-urban, and rural) with a minimum distance of 100 m. The experimental design was a RCBD with 15 progenies, three provenances, three blocks, and 20 plants per plot, totaling 900 seedlings. Results: The average percentage of polymorphic loci was 93.33%. The urban population showed a greater loss of genetic diversity (H=0.1806). 79% of the genetic diversity was found within populations. The observed gene flow value (Nm) was 1.8790, indicating that there were no random losses of alleles within populations. The fragments did not exhibit significant differences, but there were significant differences among the progenies. The stem diameter (SD) and the height-diameter relationship (H/SD) emerged as the key traits for selecting new individuals due to their higher heritability (<0.50), accuracy (<0.70), and relative coefficient of variation (<7%). Conclusion: The urban fragment is the most affected, but gene flow between fragments prevents the random loss of alleles. The analysis suggests that these fragments form a unique population, despite geographic barriers. Thus, the three fragments can be considered when choosing superior individuals for future progeny tests in genetic improvement programs for the species.
Keywords: Caroba; Genetic conservation; Genetic parameters; Progeny test